Canine adenovirus serotype 2 isolation and determination of its cultivation parameters - A. A. Klimova (Ветеринария сегодня)
Adenovirus infection in dogs caused by canine adenovirus serotype 2 predominantly results in respiratory disease typically manifested by respiratory tract lesions. Infectious laryngotracheitis is the most often recorded in dogs in the central part of the Russian Federation and its incidence tends to increase. Therefore, preventive immunization against this disease remains important. Primarily, the virus strains currently important and circulating in the particular territory shall be used for vaccine production to induce long-term and strong immunity in animals. The study was aimed at isolation of canine adenovirus type 2 remaining stable during five or more passages from the biological samples collected from animals with adenovirus infection signs as well as at determination of its cultivation parameters. As a result, five virus isolates were recovered, one of the recovered virus isolates had optimal properties for its use for vaccine production. Comparative analysis of continuous Vero, MDCK (NBL-2 and NBL-9 line) cell cultures as well as primarily trypsinized cell cultures (baby dog kidney, baby dog spleen, baby cat kidney, baby cat spleen) for their susceptibility to the recovered virus showed that MDCK (NBL-2 line) was the most susceptible. The virus cultivation parameters in this cell culture was determined at the next step. The following optimal conditions under which the virus accumulated to the maximum titres were determined: cell culture monolayer age for inoculation – 48 hours, multiplicity of infection – 0.01 TCID50/cell, preliminary holding time – 60 min, temperature – (37.0 ± 0.5) °С, cultivation period – 120 hours.